Gregorio Monreal Zia - Jimeno Aranguren , Roldán (Huarte de San Juan. Geografía e Historia, 2014)
Gregorio Monreal, Full Professor of History of Law, he has worked mainly on four main fields of knowledge. The first group is devoted to the history of the political and administrative institutions of the peninsular Basque territories; a second group is focused on the critical edition of the sources of law, singularly those of Bizkaia; a third group of articles refer to the creation of a corpus of knowledge focused on the crisis of the Basque legality (forality) in the nineteenth century, namely, the confrontation between the new Spanish legal system inspired by the liberal revolution and the ancient Basque legal systems; finally, six extensive works dedicated to the study of the history of the Basque traditional political thought, which represent an effort for exploring the Basque political thought in the Modern and Contemporary Ages. It has also developed an outstanding work in the promotion and development of academic and cultural infrastructures (UPV/EHU, Eusko Ikaskuntza, FEDHAV...).
Keywords: Gregorio Monreal; History of Law and of Institutions; Historiography of Vasconia; Historiography of Bizkaia; Historiography of Navarre